Evaluation of Patient Experiences with Nutrition Clinics in Hospital Outpatient Departments - Al-mojal, Alyah; Al-Medaimeegh, Ghadah; Almowelhi, Brooj (Pakistan Journal of Nutrition, 2019)
Background and Objective: The healthcare system has been making efforts to improve the efficiency and affordability of healthcare services by using quality-based measurements to evaluate hospitals, healthcare professionals and healthcare programs. Patient experience is considered one of the most important measurements for evaluating the quality of care in the healthcare field. This study aimed to evaluate outpatient experiences in nutrition clinics in Riyadh City and to provide opportunities for improvement. Materials and Methods: This cross-sectional study was conducted in three hospitals in Riyadh City, Kingdom of Saudi Arabia, using the “2011 Picker Survey of Outpatient Experience”. Data were collected via electronic and paper questionnaires. Participants were 217 patients (>18 years old) who had visited nutrition clinics in the previous 12 months. Results: The survey results indicated that patients lacked information regarding the person to contact (64.0%), parking spaces for their vehicles were inadequate (50.7%) and the “dietitian did not fully explain the treatment plan” (39.6%). Conclusion: This study presents an overview of outpatient experiences in nutrition clinics and identifies areas where the performance of healthcare organizations and/or health professionals is poor. Healthcare facilities could potentially improve the experience for a substantial number of patients by focusing on areas with high problem scores. In particular, the patient experience can be improved by implementing patient-centered care more broadly within healthcare organizations.